Ameliorative effect and mechanism of Si-Ni-San on chronic stress-induced diarrhea-irritable bowel syndrome in rats - Chen, Hui-Yu; Liu, Jian; Weng, Ding-Zhou; Yan, Li; Pan, Chun-Shui; Sun, Kai; Guo, Xiao; Wang, Di; Anwaier, Gulinigaer; Jiao, Ying-Qian; Li, Zhi-Xin; Han, Jing-Yan (Frontiers in Pharmacology, 2022)
Background: Chronic stress induced diarrhea is a common clinical condition, characterized by abnormal bowel movement and loose stool, which is lacking of effective treatment in clinic. Si-Ni-San (SNS) is a compound traditional Chinese medicine extensively used in China for stress related diarrhea. However, the mechanism is unclear. Methods: Male Wistar rats (200 ± 20 g) were placed in a restraint cylinder and fixed horizontally for 3 hours once daily for 21 consecutive days to establish chronic restraint stress (CRS) rat model. SNS (0.6944 g/kg or 1.3888 g/kg) was given by gavage 1 hour before restraint once daily for 21 consecutive days. We examined fecal score, dopamine β hydroxylase (DβH) and c-fos expression in locus coeruleus, norepinephrine (NE) content in ileum and plasma, expression of α1 adrenergic receptors, MLCK, MLC and p-MLC in colon and mesenteric arteries, contraction of isolated mesenteric arteries, ATP, ADP and AMP content in ileum and colon, occludin expression between ileum epithelial cells, the number of enterochromaffin cells (ECs) and mast cells (MCs) in ileum, and 5-hydroxytryptamine (5-HT) content in ileum and plasma. Results: After SNS treatment, the fecal score was improved. The increased expression of DβH and c-fos in locus coeruleus was inhibited. SNS suppressed the increased NE content in ileum and plasma, down-regulated α1 adrenergic receptors in mesenteric arteries and MLCK, MLC, p-MLC in colon and mesenteric arteries, and inhibited the contraction of mesenteric arteries. SNS also increased ATP content in ileum and colon, inhibited the decrease of ATP/ADP in ileum and ATP/AMP in colon, and up-regulated occludin expression between ileum epithelial cells. In addition, SNS inhibited the increase of ECs and MCs in ileum and the increase of 5-HT content in ileum and plasma. Conclusion: This study demonstrated that SNS could improve CRS induced abnormal feces in rats. This effect was related to inhibition of CRS induced increased expression of DβH and c-fos in the locus coeruleus, NE content in ileum and plasma and contraction of isolated mesenteric arteries; inhibition of energy metabolism abnormality and decreased occludin expression; inhibition of increased ECs and MCs in ileum, and 5-HT content in ileum and plasma.